Ecological importance of the Myrtaceae in New Zealand's natural forests. (19th January 2022) - Jo, Insu; Bellingham, Peter J.; McCarthy, James K.; Easdale, Tomás A.; Padamsee, Mahajabeen; Wiser, Susan K.; Richardson, Sarah J.
Abstract: Aims: The Myrtaceae is a woody family that plays an important role in forest ecosystems globally. The recent spread of myrtle rust, caused by a fungal pathogen ( Austropuccinia psidii ), from its native South America into New Zealand (NZ), highlights the need to quantify the ecological importance of Myrtaceae in NZ woody ecosystems. Location: New Zealand. Methods: Using NZ nationwide forest and shrubland inventory data, collected from 2009 to 2014, we quantified the ecological importance of Myrtaceae based on its richness and abundance relative to co‐occurring woody families. We then explored how climate and forest stand structure affect Myrtaceae importance in general and by tribe and growth form. Finally, we compared functional traits associated with plant growth and reproductive strategies with other dominant woody families and determined Myrtaceae's contributions to community‐weighted mean (CWM) trait values. Results: Myrtaceae occurred in 74% of the study plots and its importance value was the second highest across the woody families. It was the only one in which climbers substantially contributed to the importance value (17%). Greater Myrtaceae importance values were associated with warmer and more mesic climates and early forest successional stages. Climate associations were similar within tribes and growth forms, whereas forest structure effects varied. Myrtaceae was functionally distinct from most co‐occurring woody families. Contributions to CWM wood density, maximum height, and specific leaf area values were significantly greater than expected from its importance value. Conclusions: Myrtaceae is the second most ecologically important woody family in NZ woody ecosystems. The family has a distinctive functional trait spectrum associated with high wood density and tall stature, ensuring large and enduring carbon stocks. There will potentially be large and deleterious outcomes in forest ecosystems if taxon‐specific pathogens, such as Austropuccinia psidii, spread and significantly reduce Myrtaceae importance. Abstract : We assessed the ecological importance of Myrtaceae in New Zealand woody ecosystems under threat of myrtle rust. Myrtaceae was the second most ecologically important family and had a distinctive functional trait spectrum associated with high wood density and tall stature, ensuring large and enduring carbon stocks and, thus, potentially devastating outcomes due to taxon‐specific plant diseases, such as myrtle rust.